Utilization of Micro-Organic Minerals in Feed Based on Agroindustry by Products to Improve Ruminant Production - Muhtarudin; Widodo, Yusuf; Liman; Adhianto, Kusuma (Pakistan Journal of Nutrition, 2016)
The aims of this research were to evaluate the effects of feed supplementation with organic minerals (Zn, Cu, Se and Cr organic/micro-organic) on nutrient digestibility and ruminant performance. The research used four cattle breeds and a Latin square design. Four treatments and four replications were applied: R0 = basal feed; R1 = R0 + micro-organic minerals: 20 ppm Zn, 5 ppm Cu, 0.05 ppm Se and 0.15 ppm Cr-organic; R2 = R0 + micro-organic minerals: 40 ppm Zn, 10 ppm Cu, 0.10 ppm Se and 0.30 ppm Cr-organic and R3 = R0 + micro-organic minerals: 60 ppm Zn, 15 ppm Cu, 0.15 ppm Se and 0.45 ppm Cr-organic. The treatments had no significant effect on the rumen parameter values of NH3 or volatile fatty acids (VFAs) which were 4-12 mM and 70-150 mM, respectively, consistent with recommended values. Similarly, the treatments had no significant effects on nutrient digestibility (organic matter, dry matter, protein and crude fiber). Among the treatments, R2 yielded the highest digestibility for all nutrient types. The rates of gain were 0.68 kg/head/day for the basal treatment and 0.78, 0.8 and 1.2 kg/head/day for the organic mineral treatments. The values of feed efficiency increased with increasing organic mineral levels and were 0.22, 0.23, 0.25 and 0.30 for R0, R1, R2 and R3, respectively.